Pengelolaan Keuangan Dan Pengenalan Karakter Wirausaha Untuk Meningkatkan Keberhasilan Usaha - Treesje L Runtuwene; Agustinus Lumettu; Rudy A. J. Wowiling; Treesje A.C Langi (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Manado, 2022)
The times are increasingly demanding the participation of women in building the household economy. In today's uncertain economy, women must increase their participation through entrepreneurship. Entrepreneurship encourages women to be able to realize their ideals to help the family economy, career and self-actualization. Women prefer businesses that are in a daily environment, use feelings and tend to be personal, even carry out their business activities on the sidelines of taking care of the family routine. The business carried out is usually classified as a Micro Business (MSME) because it requires adequate knowledge to be able to develop its business, including financial management and entrepreneurial characteristics that can increase business success. From the results of observations and interviews conducted with 20 business owners in RT 26 RW 2, Malendeng Village, it is known that their business is often hampered due to lack of knowledge of financial management and entrepreneurial characteristics. This Community Service was carried out on May 29, 2022 with the lecture, question and answer method and demonstration by providing material on financial management and entrepreneurial characteristics. By knowing financial management and entrepreneurial characteristics, it is hoped that there will be an increase in business success, which in turn will result in additional income, so that women can be free from debt to cooperatives and banks.